1999
DOI: 10.1095/biolreprod61.2.458
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Human Term Placenta Is Not Increased during Labor but Can Be Massively Induced In Vitro1

Abstract: Apoptosis in human placental villi is reported to increase until close to delivery. However, the involvement of the apoptotic process in the initiation of labor, and more particularly in relation to the decrease in placental perfusion during uterine contractions, remains unknown. The purpose of the study was to examine the reactivity of the apoptotic machinery in term placentae obtained before or after the onset of labor and after in vitro incubations. The incidence of apoptotic nuclei (< 1%) as evidenced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Following 24 h of culture with Fas-Fc and cytokines, the placental explants were subjected to TUNEL assay. We and others have noted that placental villous trophoblasts undergo spontaneous apoptosis under culture conditions [35] (Fig. 3A).…”
Section: Tnf␣ and Ifn␥ But Not Il-1␤ Induce Fas-mediated Apoptosis Ofmentioning
confidence: 60%
“…Following 24 h of culture with Fas-Fc and cytokines, the placental explants were subjected to TUNEL assay. We and others have noted that placental villous trophoblasts undergo spontaneous apoptosis under culture conditions [35] (Fig. 3A).…”
Section: Tnf␣ and Ifn␥ But Not Il-1␤ Induce Fas-mediated Apoptosis Ofmentioning
confidence: 60%
“…7 On the other hand, Cirelli et al found an increase in Bax and Bcl-x and a decrease in Bcl-2 associated with increased DNA fragmentation in term placentas. 11 Bcl-2 is expressed more in term placentas than in first trimester, despite there being more apoptosis at term. 18 Another possible reason for the less significant role of the bcl family is to prolong mitochondrial function during apoptosis, as suggested by in vitro studies of human ovarian granulosa cells.…”
Section: Discussionmentioning
confidence: 95%
“…9 Consistent with the reports of in vivo detection of apoptosis in the placenta, the induction of apoptosis in the human term placenta can be demonstrated in isolated cytotrophoblasts 10 and in term placental explant cultures. 11 Our previous studies have shown that explant cultures of first trimester and term placental villi without trophic support undergo spontaneous apoptosis with a time dependent increase in the extent of low molecular weight DNA fragmentation. This induction of apoptosis can be inhibited by the addition of superoxide dismutase (SOD).…”
Section: Introductionmentioning
confidence: 98%
“…Although experiments performed with isolated placental tissue create an artificial situation, such models have the potential advantage of maintaining the placental cells in their normal histological environment and thus allowing interactions among different cell types (8,31). in this study we performed some preliminary experiments with placental tissue incubation model in order to examine the potential toxic effects of AGe-BSA in human intrauterine tissues in regard to induction of apoptosis.…”
Section: Age Induced Apoptosis In Placental Tissue Explantsmentioning
confidence: 99%